2018
DOI: 10.1007/s10072-018-3402-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in the Republic of San Marino, Italian peninsula: an incidence and prevalence study from a high-risk area

Abstract: Epidemiological studies on multiple sclerosis (MS) carried out in Southern Europe in the last years have shown a significant increase in the disease frequency. Previous surveys conducted in the Republic of San Marino, Northern Italian peninsula, identified that the population is at high risk for MS, with a prevalence of 51.6 per 100,000 population in 1982 and of 166.7 in 2005 and with a mean annual incidence of 7.9 per 100,000 for the period 1990-2005. The present work is a community-based intensive prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The high proportion (68%) of the patients with no or minimal to moderate disability (EDSS score 0-3.5) gives support to this interpretation. In our last investigation in the Republic of San Marino, using the same diagnostic criteria and case-finding procedures, the percentage of patients showing minimal moderate or no disability (EDSS score,1-3.5) was 74.6% [35]. Similarly, data compatible with improved survival have been found in other MS populations, including those from Italy [22,25,29,30,37], Norway [9], and Canada [42].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The high proportion (68%) of the patients with no or minimal to moderate disability (EDSS score 0-3.5) gives support to this interpretation. In our last investigation in the Republic of San Marino, using the same diagnostic criteria and case-finding procedures, the percentage of patients showing minimal moderate or no disability (EDSS score,1-3.5) was 74.6% [35]. Similarly, data compatible with improved survival have been found in other MS populations, including those from Italy [22,25,29,30,37], Norway [9], and Canada [42].…”
Section: Discussionsupporting
confidence: 57%
“…The descriptive surveys that have been carried out in Italy since the 1980s are characterized by a similar methodology in case-finding procedures and diagnostic criteria. Our research group, by using the same methodology, recently found a prevalence rate of 204.3 per 100,000 in the territory of the Republic of San Marino, lying within the Italian peninsula [35]. The prevalence rate we found in Ferrara was much higher than the one of the same research group estimated during 4 decades of follow-up: 26.9 per 100,000 on 1978, 46.1 per 100,000 on 1981, 69.4 per 100,000 on 1993, 121.9 on 2004 [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Worth of interest are the results of the epidemiological studies done in the Republic of San Marino, a little independent State in the Northern Italy, 150 km South from Ferrara, whose population (32,876 inhabitants) is almost exclusively Caucasian (composed by natives in San Marino, 85%, and Italy, 10%). In this State, MS prevalence increased with the same trend: 51.6/100,000 in 1984 [ 19 ], 121/100,000 in 2005 and 203/100,000 on December 31, 2014 [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of increase in the SPMS prevalence was lower than that of MS prevalence in Newcastle, Australia [ 104 , 105 ]; Csongrad County, Hungary [ 32 , 33 ]; Catania, Italy [ 51 53 ]; Ferrara, Italy [ 44 , 46 ]; Swietokrzyskie Province, Poland [ 62 , 63 ]; and Isle of Man, UK [ 102 ]. The proportion of increase in the SPMS prevalence was higher than that of MS prevalence in the Republic of San Marino, Italy [ 41 , 45 ]; Ferrara, Italy [ 43 , 44 ]; and Leeds, UK [ 97 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 MS moderate-quality studies reported the proportion of SPMS patients and thus were included in this meta-analysis [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. The pooled prevalence of SPMS was 22.49 (99% CI: 14.97, 31.48)/100,000 (Fig.…”
Section: Italymentioning
confidence: 99%